Seismic Performance of Geosynthetic-Encased Stone Columns. Issue 1 (January 2014) - Guler, Erol; Alexiew, Dimiter; Abbaspour, Aiyoub; Koc, Mustafa
The geotextile-encased columns (GECs) foundation system for embankments on soft or problematic soils was introduced in 1994. The GECs consist of compacted granular fill similar to common stone columns, but with a main decisive difference: GECs are confined in a high-strength woven geotextile cylinder (encasement). Consequently, they work properly even in extremely soft soils. Granular columns under compressive loads experience different failure modes, such as bulging, general shear failure, and sliding. However, the most common failure mode for stone columns in soft clays is bulging. With the help of GECs, the bulging failure can be prevented. The risk of bulging is even higher for earthquake loading conditions. A vast amount of numerical, analytical, and experimental research has been done to study different aspects of GEC's behavior. Despite this available literature from several researchers, there is not much research, numerically or experimentally, about the seismic behavior of GECs. To analyze the effect of earthquakes on stone columns and to determine how the presence of GECs improves the soil behavior, three-dimensional finite element analysis was used. The results show that the encapsulation of the stone column by a geosynthetic reinforcement (i.e., instead of installing ordinary stone columns, using geosynthetic-encapsulated columns) helps with the integrity of the column and also improves the system behavior under earthquake loading conditions.